2014
DOI: 10.1021/ol502373u
|View full text |Cite
|
Sign up to set email alerts
|

Direct Intramolecular Conjugate Addition of Simple Alkenes to α,β-Unsaturated Carbonyls Catalyzed by Cu(OTf)2

Abstract: An unprecedented intramolecular conjugate addition of simple alkenes to α,β-unsaturated carbonyl compounds has been developed. A simple Lewis acid such as Cu(OTf)2 was found to effectively catalyze the reaction, and six- and five-membered cyclic products were obtained in moderate to high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 40 publications
2
19
0
Order By: Relevance
“…On the other hand, the aza‐Prins‐type exo cyclization of an imine bearing an alkene moiety on the imine carbon is relatively rare, while useful cyclic compounds having a protected amino group can be obtained (Scheme b) . To the best of our knowledge, there have been few reports on the endo cyclization and no descriptions on the catalytic asymmetric variant (Scheme c) . In this context, we became interested in the formation of 1‐aminoindene derivatives 3 by the acid‐catalyzed aza‐Prins‐type endo cyclization by using 2‐alkenylbenzaldehydes 1 through the in situ generation of the iminium salt 2 .…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, the aza‐Prins‐type exo cyclization of an imine bearing an alkene moiety on the imine carbon is relatively rare, while useful cyclic compounds having a protected amino group can be obtained (Scheme b) . To the best of our knowledge, there have been few reports on the endo cyclization and no descriptions on the catalytic asymmetric variant (Scheme c) . In this context, we became interested in the formation of 1‐aminoindene derivatives 3 by the acid‐catalyzed aza‐Prins‐type endo cyclization by using 2‐alkenylbenzaldehydes 1 through the in situ generation of the iminium salt 2 .…”
Section: Methodsmentioning
confidence: 99%
“…This result suggested that the present cyclization can proceed through aza‐Prins reaction including the carbocation intermediate as shown in Scheme , whereas an alternative pathway via electrocyclic reaction cannot be ruled out. When p ‐toluenesulfonamide (TsNH 2 ) was used instead of BocNH 2 , 1‐aminoindene derivative 3 q was obtained in good yield …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations